Study on the bio-functionalization of memristive nanowires for optimum memristive biosensors. Issue 12 (3rd March 2016) - Tzouvadaki, I.; Madaboosi, N.; Taurino, I.; Chu, V.; Conde, J. P.; De Micheli, G.; Carrara, S.
Abstract : Semiconductor nanowires are emerging as promising building blocks for biosensors enabling direct electrical detection of various biomolecules. Abstract : Semiconductor nanowires are emerging as promising building blocks for biosensors enabling direct electrical detection of various biomolecules. In this framework, two-terminal Schottky-barrier silicon (Si) nanowire arrays that exhibit memristive electrical response, so-called memristive devices, are bio-functionalized and converted to memristive biosensors for bio-detection purposes. A comparative analysis of three bio-functionalization strategies is proposed here in order to design and develop optimum memristive biosensors to be implemented in label-free sensing applications. The surface of the device is modified with an anti-free-Prostate Specific Antigen (PSA) antibody as the case of study via : (a) direct adsorption on the device surface, (b) a bio-affinity approach using biotin–streptavidin combination and (c) covalent attachment using (3-glycidyloxypropyl)trimethoxysilane (GPTES). The optimum memristive biosensor is defined via the calibration and comparative study of the biosensors' electrical response under controlled environmental conditions (humidity and temperature) in order to maximize the performance of the biosensor. In addition, it is demonstrated that the direct passive adsorption strategy presents double the performance of the other two methods. The uptake of biological molecules on the nanostructure surface is verified by atomic force microscopy and confocal microscopy. Scanning electron microscopy reveals the details of the surface morphology of the nanofabricated structures before and after bio-functionalization for the three methods applied. The system shows potential for general application in molecular diagnostics, and, in particular, for the early detection of prostate cancer.